BIOSOCIAL AND PSYCHOGENETIC APPROACHES IN THE STUDY OF ALTRUISM - Humeniuk, Yuly (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The modern problems of philosophy are the problems of the individual and society. All the philosophical constructs of the essence and origin of altruism indicate the insufficiency of biological knowledge about man and the need for the development of a philosophical theory of egoism and altruism in the natural scientific direction. In this context, two controversial questions need to be resolved: why has the biosphere not turned into a realm of global friendship and mutual assistance to do vital tasks with joint efforts, and how can cooperation and altruism arise in the process of evolution, if its driving force is the mechanism of natural selection? The aim of the research is to conduct a review of scientific sources in the field of sociobiology and psychogenetics, which reveal the general sociobiological essence of altruism, the biological origin of this phenomenon and its evolutionary significance for humans. Research methodology involves an interdisciplinary methodological approach, a systematic methodological approach, the method of historiographical analysis, comparative analysis, methods of theoretical research, analysis and synthesis. Research results. It was found that altruism is the ability to care about others, to sacrifice oneself for the sake of others, contributes to the continuation of the family and forms the level of well-being and survival of humanity in general. Egoism and altruism are oppositely directed models of evolutionary behavior and play an important role in the formation of social relations. These two phenomena are controlled by a single mechanism of psychogenetic heredity. In this vein, quite contradictory theories are considered - the concept of the "altruistic gene" by V. Efroimson and of the "selfish gene" by R. Dawkins. Discussion. The results of experimental studies indicate that no psychological trait or feature of human behavior is formed without the participation of hereditary factors. The manifestation of egoism in the majority occurs without the participation of consciousness, automatically; the manifestation of altruism is associated with a more developed intelligence. But the natural dualism between altruism and egoism enables each individual to survive both as a separate organism and as a member of society. Egoism and altruism are two antagonistic manifestations of some qualities of an individual human character, which depend on both the fate of an individual and his loved ones, as well as the direction of the historical development of all mankind. Conclusions. It is known that almost every person is prone to altruism as well as to egoism, and the nature of their actions depends on the situation. But there are also more permanent trends of behavior that depend on culture and moral norms, as well as on innate features of the psyche. When studying altruism, one always takes into account the natural duality between selfishness and altruism, which is manifested in the behavior of animals and humans. The problem of altruism, remaining even today a "cornerstone" for biologists, geneticists, philosophers and representatives of the humanities and theology, education, pedagogical sciences, social behavioral sciences, needs its solution, in particular the definition and establishment of the place of the phenomenon of altruism in the spectrum of ethical categories.